Development and characterization of sustainable clay-cement composite bricks reinforced with coconut fibre and rice husk ash - Mustapha, Kabiru; Abdulraman, Sikiru Ottan; Adepoju, Suraju Adesina; Egbanubi, Oluwatosin Eunice (Kathmandu University Journal of Science Engineering and Technology, 2025)
This study investigates the development of clay-cement composites reinforced with coconut fibre and cement partially replaced with rice husk ash (RHA) for brick applications. Conventional fired and unfired clay bricks are often limited by high energy consumption, environmental impact, and low mechanical strength. To address these challenges, this study explores the incorporation of agricultural wastes (coconut fibre) and RHA to enhanced mechanical and microstructural performance. Clay-based composite bricks were developed by partially replacing cement with rice husk ash (RHA) and reinforcing the mixture with 0–25 vol.% coconut fibre. The composite system incorporates coconut fibre as the primary reinforcement, while rice husk ash functions solely as a pozzolanic partial replacement for cement. Physical, chemical and microstructural characterization of the clay and RHA was conducted using hydrometer analysis, X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), and Scanning Electron Microscopy (SEM). The XRD analysis revealed that the clay was rich in kaolinite, while RHA contained 66.95% SiO2, providing pozzolanic activity for improved bonding. The effects of varying fibre volume fractions (0–25% coconut fibre) on the mechanical properties were evaluated, with optimal compressive strength (2.89 MPa) obtained at 20 vol.% coconut fibre, while the optimum flexural strength and fracture toughness were obtained at 15 vol.% with values of 4.61 MPa and 1.23 MPa√m respectively. Microstructural analysis by SEM revealed enhanced fibre-matrix interaction and reduced porosity. Comparisons with conventional sandcrete and fired clay bricks demonstrated that the optimized composite exhibited competitive performance. These findings demonstrate the potential for utilizing coconut fibre and RHA in sustainable brick production, offering improved mechanical performance while contributing to environmental sustainability and cost-effectiveness in building materials.